Rheology as a tool to predict the release of alpha-lipoic acid from emulsions used for the prevention of skin aging - Isaac, Vera Lucia Borges [UNESP]; Chiari-Andréo, Bruna Galdorfini [UNESP]; Marto, Joana Marques; Moraes, Jemima Daniela Dias [UNESP]; Leone, Beatriz Alves [UNESP]; Corrêa, Marcos Antonio [UNESP]; Ribeiro, Helena Margarida (Hindawi, 2015)
The availability of an active substance through the skin depends basically on two consecutive steps: the release of this substance from the vehicle and its subsequent permeation through the skin. Hence, studies on the specific properties of vehicles, such as their rheological behavior, are of great interest in the field of dermatological products. Recent studies have shown the influence of the rheological features of a vehicle on the release of drugs and active compounds from the formulation. In this context, the aim of this study was to evaluate the influence of the rheological features of two different emulsion formulations on the release of alpha-lipoic acid. Alpha-lipoic acid (ALA) was chosen for this study because of its antioxidant characteristics, which could be useful for the prevention of skin diseases and aging. The rheological and mechanical behavior and the in vitro release profile were assayed. The results showed that rheological features, such as viscosity, thixotropy, and compliance, strongly influenced the release of ALA from the emulsion and that the presence of a hydrophilic polymer in one of the emulsions was an important factor affecting the rheology and, therefore, the release of ALA.